Validating estimates of problematic drug use in England - Heatlie Heath; Frisher Martin; Hickman Matthew (BMC, 2007)
Abstract Background UK Government expenditure on combatting drug abuse is based on estimates of illicit drug users, yet the validity of these estimates is unknown. This study aims to assess the face validity of problematic drug use (PDU) and injecting drug use (IDU) estimates for all English Drug Action Teams (DATs) in 2001. The estimates were derived from a statistical model using the Multiple Indicator Method (MIM). Methods Questionnaire study, in which the 149 English Drug Action Teams were asked to evaluate the MIM estimates for their DAT. Results The response rate was 60% and there were no indications of selection bias. Of responding DATs, 64% thought the PDU estimates were about right or did not dispute them, while 27% had estimates that were too low and 9% were too high. The figures for the IDU estimates were 52% (about right), 44% (too low) and 3% (too high). Conclusion This is the first UK study to determine the validity estimates of problematic and injecting drug misuse. The results of this paper highlight the need to consider criterion and face validity when evaluating estimates of the number of drug users.